Taxonomic studies on the genus Delphinium (Ranunculaceae) from China (XXVI): Notes on D. altissimum and D. scabriflorum, with description of a new species, D. pseudoscabriflorum - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2023)
Based on literature consultation and specimen survey, we demonstrate that the Himalayan species Delphinium scabriflorum (Ranunculaceae) has been largely misunderstood. We agree with the previous treatment of placing D. altissimum in synonymy with D. scabriflorum. We determine that those specimens from Bhutan previously referred to D. scabriflorum and those from Cona in China’s southern Xizang (Tibet) previously referred to D. conaense or D. umbrosum var. drepanocentrum represent a new species, which we describe as D. pseudoscabriflorum herein. This species, currently known only from Bhutan and the closely adjacent Cona county in southern Xizang, China, is similar to D. ludlowii, a species endemic to Bhutan, and D. scabriflorum, a widely distributed Himalayan species, but differs by an array of characters with respect to leaf division, pedicel indumentum, shape of bracteoles and their position on the pedicel, shape of sepaline spurs, and follicle pubescence.